Analisis Faktor-Faktor Yang Mempengaruhi Produksi Kubis (Brassica Oleracea) - Veronica Da Costa (Fakultas Pertanian, 2021)
The overplus of vegetables like potato or cabbage that other plants is have high productivity, easy marketing, and have stable price, so that’s really profitable from economic point of view. Vegetable management that use high chemical input, aviability of high quality seed, and pests or plant desease causing low quality vegetables, high cost production, and high risk of crop failure is because of the ability of farmers in efficient vegetable management. Research population is the active cabbage farmer at Tulungrejo, Bumiaji, Batu. Research location is designed because this area is a centre of cabbage production and cabbage is prime product in Bumiaji. The independent variable is : Area production, seed amount, fertilizer, workers, and pestiside. Dependent variable is Total production. Analysis methods using descriptive analysis for hipotesis test 1 and regretion analysis for hipotesis test 2.